2021
DOI: 10.1002/anie.202103039
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Reactivity of Uranyl Superoxide

Abstract: The high radiation field associated with spent nuclear fuel (UIVO2) pellets produces an array of reactive radical species that impact the corrosion and formation of secondary alteration phases. Dioxygen radicals are important as radiolysis products, but the interaction between these reactive oxygen species and UVIO22+ and its effects on the resultant alteration phases is unclear. We report the first example of a UVI superoxide compound and explore its reactivity in the environments relevant to the storage of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 54 publications
2
44
0
Order By: Relevance
“…Our findings suggest that at 0.5 h, the adsorption of U onto POM is the primary reaction between NOM and U–KCl, while the precipitation of U–K-bearing crystalline solids is evident after 24 h of reaction. Carbonation reactions in the presence of U­(VI) have been previously observed within these time scales, and the surface of the POM could facilitate heterogeneous nucleation of U–K-bearing crystals as the reaction time progresses from 0.5 to 24 h. Our results are unique given that other studies only focused on the adsorption of U onto organic material . However, other investigations have shown that other metal ions adsorbed to POM can lead to the growth of metal–NOM crystalline phases .…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Our findings suggest that at 0.5 h, the adsorption of U onto POM is the primary reaction between NOM and U–KCl, while the precipitation of U–K-bearing crystalline solids is evident after 24 h of reaction. Carbonation reactions in the presence of U­(VI) have been previously observed within these time scales, and the surface of the POM could facilitate heterogeneous nucleation of U–K-bearing crystals as the reaction time progresses from 0.5 to 24 h. Our results are unique given that other studies only focused on the adsorption of U onto organic material . However, other investigations have shown that other metal ions adsorbed to POM can lead to the growth of metal–NOM crystalline phases .…”
Section: Discussionmentioning
confidence: 60%
“…The dioxygen radicals can invoke further mineralization processes and have previously been shown by Kravchuk and Forbes to degrade phosphonate molecules to the inorganic phosphate by breaking a C–P bond . In addition, Kravchuk et al also demonstrated that U­(VI) can stabilize superoxide radicals and promote carbonation processes that specifically resulted in the formation of uranyl peroxide carbonate complexes and the grimselite phase through a solid-state transformation . Both Kravchuk et al and Blanes Díaz et al also noted that photochemical degradation of U­(VI) organic materials can take place in the solid state, and so these mineralization reactions may indeed occur following adsorption to the POM phase …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The O–O bond length of the superoxido ligand in the 2D uranyl sheet is 1.34 Å, close to that of the naked one (1.33 Å) as well as that of a recently reported uranyl superoxide compound (1.39 Å). 79 …”
Section: Resultsmentioning
confidence: 99%
“…Besides, the aforementioned techniques are unable to reveal chemical information on speciation or bonding, hence it is difficult for them to identify the structural information of uranyl compounds. As reported in the studies, many techniques, including FTIR, 9,10 Raman, 11,12 electrospray ionization mass spectrometry, 13,14 and X-ray absorption fine structure spectroscopy (XAFS), 15,16 have been utilized to reveal the chemical information of uranyl compounds. Electrospray ionization mass spectrometry can provide coordination information through dissecting the fragment ion peaks of pyrolysis products, and thus speculating the chemical structures of uranyl compounds.…”
Section: Introductionmentioning
confidence: 99%